A generalized empirical likelihood approach for two-group comparisons given a U-statistic constraint. Issue 2 (3rd March 2016) - Yu, Jihnhee; Yang, Luge; Vexler, Albert; Hutson, Alan D.
Abstract : We investigate a generalized empirical likelihood (EL) approach in a two-group setting where the constraints on parameters have a form of U -statistics. In this situation, the summands that consist of the constraints for the EL are not independent, and a weight of each summand may not have a direct interpretation as a probability point mass, dissimilar to the common EL constraints based on independent summands. We show that the resulting EL ratio statistic has a weighted χ 2 distribution in the univariate case and a combination of weighted χ 2 distributions in the multivariate case. Through an extensive Monte-Carlo study, we show that the proposed methods applied for some well-known U -statistics have robust Type I error control under various underlying distributions including cases with a violation of exchangeability under null hypotheses. For the application, we employ the proposed methods to test hypotheses in crossover designs demonstrating an adaptability of the proposed methods in various hypothesis tests.